Strategic directions of tax policy of Ukraine in the sphere of industrial development regulation - Vishnevskiy, V.P.; Chekina, V.D. (Економіка промисловості, 2014)
It was determined that tax policy of Ukraine strategically remains in the state of uncertainty. We need the clear definition and consistent observance of long-term priorities of social and economic development in a whole and the taxation in particular, that maintain stability of business operations and are of key importance for investment decisions making. The global financial and economic crisis of 2008-2009 has demonstrated that the EU is going through the hard times nowadays and obviously loses the global economic competition to the South. The directive toward the economic integration with EU goes against the Ukrainian economic interests at least in point of development prospects of industry which as it is shown firstly is a generally accepted generator of economic innovations and secondly is still the leading sector of the national economy that supports close cooperation ties with countries of the Custom Union (CU). Ukraine relates to the post-Soviet countries with incomes that are below average. In this connection, it is necessary to solve the problems, which are typical for developing countries and to find new growth opportunities related to including of value generation in global chains focused on the South, which is on the upswing in a present historical period. That is why at the present time, it makes sense to develop the tax system with caution to the developing countries, which also use the achievements of modern economic theory. In this connection, the experience of the tax incentives in successful developing countries (China, India, Brazil, South Africa, the Russian Federation, Kazakhstan and Belarus) was reviewed. The proposals for the strategic directions of tax policy of Ukraine in the sphere of regulation of the industry were grounded. The main directions of tax policy for mid-term (5-7 years) should be the creation of favorable conditions for innovative development by means of provision of efficient tax incentives for scientific, research and innovative activity. The strategic direction of tax policy for long-term perspective (10-15 years) should be the creation of favorable conditions for the sustainable development of the country and neoindustrialization by means of shifting from income taxation to levying of resource usage and gradual transition to the principles of "green" tax reform.